Unique genetic and risk-factor profiles in clusters of major depressive disorder-related multimorbidity trajectories - Gezsi, Andras; Van der Auwera, Sandra; Mäkinen, Hannu; Eszlari, Nora; Hullam, Gabor; Nagy, Tamas; Bonk, Sarah; González-Colom, Rubèn; Gonda, Xenia; Garvert, Linda; Paajanen, Teemu; Gal, Zsofia; et al. (Nature communications, 2024)
The heterogeneity and complexity of symptom presentation, comorbidities and genetic factors pose challenges to the identification of biological mechanisms underlying complex diseases. Current approaches used to identify biological subtypes of major depressive disorder (MDD) mainly focus on clinical characteristics that cannot be linked to specific biological models. Here, we examined multimorbidities to identify MDD subtypes with distinct genetic and non-genetic factors. We leveraged dynamic Bayesian network approaches to determine a minimal set of multimorbidities relevant to MDD and identified seven clusters of disease-burden trajectories throughout the lifespan among 1.2 million participants from cohorts in the UK, Finland, and Spain. The clusters had clear protective- and risk-factor profiles as well as age-specific clinical courses mainly driven by inflammatory processes, and a comprehensive map of heritability and genetic correlations among these clusters was revealed. Our results can guide the development of personalized treatments for MDD based on the unique genetic, clinical and non-genetic risk-factor profiles of patients. Major depressive disorder is a heterogeneous condition with varied presentation of symptoms, comorbidities, and related genetic factors. This study aimed to identify clusters of major depressive disorder-related longitudinal multimorbidity trajectories and to characterize the clusters using genetic and risk factor data.